732 TEE role in patients selection for transcatheter edge to edge tricuspid repair. (8th December 2021) - Filippis, Aurelio De; Nobile, Edoardo; Paolucci, Luca; Vitez, Luka; Bono, Maria Caterina; Carpenito, Myriam; Cammalleri, Valeria; Mega, Simona; Nusca, Annunziata; Grigioni, Francesco; Ussia, Gian Paolo
Abstract: Aims: The natural history of tricuspid valve (TV) regurgitation is characterized by dismal prognosis and high in-hospital mortality when treated with isolated TV surgery. Although the anatomy and the imaging of the TV are very challenging, the edge-to-edge repair with the TriClip (Abbott Vascular, Santa Clara, CA) showed promising results. We report preliminary results of our experience with the TriClip System in a cohort of 'real life' patients with functional tricuspid regurgitation (TR). Methods and results: From January to September 2021, 30 consecutive patients with severe TR has been screened, 8 underwent transcatheter TriClip repair. The anatomical feasibility was established according to a complete transesophageal echocardiogram (TEE) and a dedicated CT scan for the right cardiac chambers. All the echocardiographic projections focused on right ventricle were used during the procedure, with the aim of optimizing the visualization of the catheters and device with respect to the anatomical structures of the tricuspid valve complex. The procedure was conducted under general anesthesia, guided by TEE and fluoroscopy. In-hospital and 30-day clinical and echocardiographic outcomes were recorded. The annulus septo-lateral diameter was enlarged in all cases, and functional TR was present in all patients. In two patients, the pacemaker lead interfered with leaflets coaptation. TR jet was predominantly central. The implant and procedural success were achieved in all cases, implanting one device in five patients and two in three patients. The final TR grade was 2+ in four patients and and 1+ in the others. All patients were extubated in the catheterization laboratory. There were no procedural or in-hospital adverse events. At 30-day follow-up, we observed significant improvement in clinical and echocardiographic outcomes. Conclusions: In our experience, 26% of screened patients were selected for the procedure. Favourable anatomical findings for the TV edge-to-edge repair were the following: moderate leaflet tethering (coaptation depth <10 mm); large annulus but with small coaptation gap (<7 mm); antero-septal or postero-septal jet location; commissural jet; small right ventricular dimensions; pacemaker lead with no leaflet tethering. The best transcatheter approach consists of obliterating the antero-septal coaptation rim for a more favourable angle between the inferior vena cava and valvular plane. High-quality TEE imaging during the procedure is required for obtaining procedural success. Patient selection and tricuspid valve anatomy characterization with TEE and cardiac CT scan is critical for procedural success and clinical improvements.